Ship's Surgeons of the Dutch East India Company Commerce and the Progress of Medicine in the Eighteenth Century - Bruijn, Iris (LUP Academic, 2009)
The ship's surgeons in the employ of the Dutch East India Company were responsible for the healthcare on board the ships and in the hospitals founded by the Company in a vast geographical area expanding from South Africa to Japan. They were not highly regarded by their contemporaries, who criticised them for being little more than barbers or loblolly boys. The author of this fascinating study paints the true picture of the profession, drawing on her analysis of data for some 3,000 ship's surgeons in the Company's service, and including the recruitment policy of the Company, the career of the surgeons, their geographical origins, their life expectancy, to mention but a few. The results of her analysis, based on many hitherto unpublished sources, show this negative image to be a myth. The surgeons were, as a rule, fairly well educated according to the standards of their time. The tragic fact that they were confronted with diseases unknown in Europe and incurable at the time contributed to the sailors' and the society's dismissive attitude to their skills.